2006
DOI: 10.1111/j.1439-0523.2006.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of photoperiod on the Vrn‐H2 locus (4H) which is a major determinant of plant development and reproductive fitness traits in a facultative × winter barley (Hordeum vulgare L.) mapping population

Abstract: To determine the effect of Vrn-H2 locus on plant developmental and agronomic traits, detailed controlled environment tests involving a factorial set of vernalization and photoperiod treatments were carried out using doubled haploid lines developed from a facultative (Vrn-H2 ) ) · winter (Vrn-H2 + ) barley cross. The allele phase at the Vrn-H2 locus influenced heading date as well as the developmental and agronomic traits. The performance of Vrn-H2 + lines was significantly influenced by vernalization: reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Combinations of alleles at the VRN-1 and PPD-1 loci have been reported to result in variation in agronomic traits and physiological development such as flowering time [ 20 , 21 , 22 ], tillering, spikelet number, and plant height [ 9 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of alleles at the VRN-1 and PPD-1 loci have been reported to result in variation in agronomic traits and physiological development such as flowering time [ 20 , 21 , 22 ], tillering, spikelet number, and plant height [ 9 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vernalization affects not only heading time, but also the relative duration of phases of plant development. Thus, different combinations of vernalization alleles might affect the balance of number of tillers and spike size, even within the same maturity group (Karsai et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence, however, that secondary and interaction effects may also regulate these loci, i.e. photoperiod on VRN loci ( von Zitzewitz et al , 2005 ; Dubcovsky et al , 2006 ; Karsai et al , 2006 ; Szűcs et al , 2006 ; Trevaskis et al , 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Photoperiod duration also affects ZCCT activity: a level of expression occurs under long, but not short photoperiods ( Dubcovsky et al , 2006 ; Trevaskis et al , 2006 ). The connection between photoperiod sensitivity and the allele phase of the VRN-H2 locus was also identified via functional QTL analyses ( Karsai et al , 2006 ). Trevaskis et al (2006) demonstrated that ZCCT-H gene expression levels fluctuate on a daily basis, suggesting that this gene is under circadian clock control.…”
Section: Discussionmentioning
confidence: 99%